An Ethnobotany-Based Biodiversity Module for Improving Students' Science Process Skills and Critical Thinking Skills - Kusumaningrat; Samsurizal M Suleman; I Made Budiarsa; Astija; Muhammad Jamhari (Universitas Pendidikan Ganesha, 2026)
Science learning at the junior high school level still faces challenges in the form of low science process skills and students’ critical thinking skills due to the use of learning materials that are less contextual and have not integrated environmental potential as a learning resource. This condition causes students to become passive during the learning process and experience difficulties in connecting biodiversity concepts with real-life experiences. This study aims to analyze learning needs, develop, and evaluate the feasibility of an ethnobotany-based biodiversity module in improving junior high school students’ science process skills and critical thinking skills. The study employed a Research and Development (R&D) approach using the ADDIE model involving 32 seventh-grade students as the trial subjects. Data were collected through observations, interviews, expert validation sheets, user response questionnaires, and essay tests. The research instruments included validation sheets, practicality questionnaires, and tests of science process skills and critical thinking skills. Data were analyzed using quantitative descriptive analysis techniques and product feasibility interpretation. The findings indicate that the developed module meets the criteria of validity, practicality, and effectiveness for science learning implementation. The ethnobotany-based module facilitates exploratory learning activities based on the surrounding environment and encourages students’ active involvement in observation, classification, data analysis, and scientific argumentation. This study concludes that the ethnobotany-based biodiversity module is an effective instructional innovation for supporting contextual and meaningful science learning.